Analysis of Shared Value Influencing Millennial Generation Civil Servants in Online Spending Using Ethnographic Methods Case Study: Ministry X - Utami, Sri; Heikal, Jerry (Economic Reviews Journal, 2025)
The millennial generation is one of the most active groups in utilizing digital technology, including online shopping, which has become an integral part of modern lifestyles. Millennial State Civil Apparatus (ASN) hold significant potential as digital consumers due to their substantial numbers and their tendency toward practical, fast, and secure consumption patterns. However, research on the values influencing online shopping decisions among ASN remains limited. This study aims to analyze the shared values that shape online shopping behavior of millennial ASN using a qualitative approach with ethnographic methods. Data were collected through participatory observation and in-depth interviews with five millennial ASN aged 31–38 years. Data analysis employed coding techniques to identify dominant values and their intersections across respondents. The findings indicate that despite variations in shopping frequency, product types, and personal motivations, two primary values consistently emerge as shared values: promotions and security. Promotions, including price discounts, vouchers, and free shipping, serve as the main drivers of purchasing decisions, while security plays a crucial role in building trust toward e-commerce platforms. These results provide both academic insights and practical implications for developing digital business strategies targeting millennial ASN.